COMPARISON OF INTRAPERITONEAL AND INTRADUCTAL ROUTES IN THE GROWTH OF N-METHYL-N-NITROSOUREA-INDUCED BREAST CANCER IN SPRAGUE DAWLEY RATS: A SYSTEMATIC REVIEW 2014–2024 - Prameswari, Adilla Soraya; Sompokan, Ruendhita Azzahra Sari; Annisa, Annisa; Putri, Rachma Greta Perdana; Yuniasih, Dewi; Danian, Muhamad; Tianotak, Muhammad Tri Yoga (Folia Medica Indonesiana, 2025)
Breast cancer is one of the[-6pc]AU: Please provide affiliations for your paper. leading causes of death for women worldwide, characterized by malignant tumors in the mammary epithelium. Breast cancer modelling using Sprague Dawley animals induced by N-Methyl-N-Nitrosourea (MNU) compounds is commonly used through various administration routes. The intraperitoneal route is the conventional route and the intraductal route is a new route capable of directly targeting the mammary ducts. Both routes affect the speed and characteristics of breast cancer cells in experimental animals. This systematic review using PubMed and Scopus databases from 2014-2024 aims to compare the effects of intraperitoneal and intraductal administration routes on breast cancer induction and the similarities in histopathological characteristics and biomarkers with human breast cancer cells. Of the 324 articles, 15 met the inclusion criteria showing that the intraductal route induces tumors faster (6–8 weeks) with Ductal Carcinoma In Situ (DCIS) type, ER+/PgR+ expression, and low Ki-67 index, resembling the luminal A subtype. The intraperitoneal route requires 8–12 weeks, producing multiple tumors with a high Ki-67 index, resembling luminal B. Administration of additional substances such as PF4, white tea, and physical activity are anti-tumorigenic, while radiation and a high-fat diet are pro-tumorigenic. Therefore, the intraductal route can be used as the main choice in selecting the route of administration of MNU induction.